Plant collections from Bangladesh in the herbarium at Shillong (Assam), India (Bangladesh Journal of Plant Taxonomy, 2010)
The paper presents a complete list of plants from Bangladesh deposited in the herbarium of the Botanical Survey of India at Shillong (ASSAM). A total of 448 species belonging to 324 genera and 101 families has been found to be deposited in the herbarium in Assam. Detailed field data of each species have also been provided.Keywords: Bangladesh; Plant collections; Assam.DOI: 10.3329/bjpt.v17i2.6695Bangladesh J. Plant Taxon. 17(2): 141-165, 2010 (December)